TASAWUF SEBAGAI AKHLAK: SEBUAH JALAN MENAPAKI TASAWUF PADA ABAD 21 - Endrika Widdia Putri (JURNAL AL-AQIDAH, 2022)
This article describes Sufism as a moral that can be applied in the 21st century. It is analyzed using a qualitative approach with exploratory and analytical methods. The results of this study are that Sufism as morality is a method/way to carry out the practice of Sufism in everyday life. Unlike tasawuf as a maqam, which must be organized or in order to live it, 21st century humans must follow a tarekat or require step by step in practice, tasawuf as morals does not have to be like that. In the 21st century, it is enough for humans to make the existing conceptions of Sufism as an attitude, behavior and actions, or to present the values of Sufism in the reality of their life. Also, you can choose any tasawuf conception that you want to contextualize according to the situation and conditions, without having to be systematized.